La notion de « structure » entre anthropologie, études littéraires et littérature - Pauline Mettan (Contextes)
The semantic plasticity of the notion of “structure” has quickly become commonplace in studies on the subject. The aim here is not to add a new definition to the list, but to consider its circulation between disciplines, its uses and the values that it carries. I start with a quick overview of the circulation of the notion of structure from hard sciences to social sciences. I then focus more specifically on its appropriation by literary scholars of Proust’s La Recherche in the 1960s-1970s. The latter (Roland Barthes, “Proust et les noms” (1966), Gérard Genette, “L’âge des noms” (1976)) have indeed built upon Proust’s reflection on proper nouns to elaborate and justify a new "structural" method of reading texts. I question structuralist literary critics’ take on the notion of structure and on Proust’s work. Lastly, I turn to what structural analysis owes to Proust’s thought.